2009
DOI: 10.3233/jad-2009-1141
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Aversive but not in Safe Taste Memory in the APPswe/PS1dE9 mice

Abstract: Age-related changes in taste memory were evaluated in APPswe/PS1dE9 transgenic (Tg) mice and age-matched wild type littermate controls (Wt). These Tg mice produce increasing amounts of amyloid-beta in the brain with age, develop significant amounts of plaques by 9 months of age, and provide an opportunity to study the effects of Alzheimer's disease-like amyloidosis on different aspects of taste memory. In groups of mice ranging from 15-16 months of age, the neophobic response and its attenuation were similar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Consistent with the work of other groups (Reiserer et al. , 2007; Ramirez‐Lugo et al. , 2009), we observed that the untreated AD transgenic mice demonstrated statistically significant impairments in their cognitive memory performance across the training trials (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the work of other groups (Reiserer et al. , 2007; Ramirez‐Lugo et al. , 2009), we observed that the untreated AD transgenic mice demonstrated statistically significant impairments in their cognitive memory performance across the training trials (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The APP/PSEN1 TG mice were behaviorally characterized in multiple studies [ 91 , 92 ] demonstrating amyloidosis as early as 4–6 months [ 68 , 71 ], which was linked to behavioral decrements in spatial learning, including decrements in WM due to synaptic changes [ 69 , 77 , 93 ]. However, the functional changes in this strain of mice do not always temporally correlate with elevated Aβ levels in the brain and thus, a selection of appropriate behavioral (and electrophysiological) endpoints is critical for evaluation of progressive AD-related pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, deficits in taste aversion learning -in which ingestion of a flavoured liquid is followed some time later with illness -have been reported in 2-5 month old APPswe/PS1dE9 mice [18,61].…”
Section: Discussionmentioning
confidence: 99%